Outcomes of Pulmonary Endarterectomy Operation Concomitant with Cardiac Procedures - Erdem, Hasan; Korun, Oktay; Yanartaş, Mehmed; Taş, Serpil; Erden, Benay; Yerlikhan, Onur; Erkilinç, Atakan; Kaymaz, Cihangir; Sunar, Hasan; Yildizeli, Bedrettin (The Thoracic and Cardiovascular Surgeon, 2020)
Background The aim of this study was to analyze the results of pulmonary endarterectomy (PEA) performed simultaneously with additional cardiac procedures in a single tertiary-level center.Methods Data of patients who underwent PEA with additional cardiac procedures for chronic thromboembolic pulmonary hypertension (CTEPH) in our clinic were retrospectively reviewed using patient records.Results Between March 2011 and April 2019, 56 patients underwent PEA with additional cardiac surgery. The most common additional procedure was coronary artery bypass grafting (21 patients; 38%). The median intensive care unit and hospital stays were 4 (3–6) days and 10 (8–14) days. Mortality was recorded in six patients (11%). In multivariate analysis, only preoperative pulmonary vascular resistance (PVR) (p = 0.02; odds ratio [OR]: 1.003) and cardiopulmonary bypass duration (p = 0.02; OR: 1.028) were associated with mortality. When the cutoff value of 1000 dyn.s.cm−5 was taken in the receiver operating characteristic curve analysis, preoperative PVR predicted mortality with 83% sensitivity and 94% specificity (area under curve = 0.89; p < 0.01).Conclusion PEA for CTEPH may be performed safely with other cardiac operations. This type of surgery is a complex procedure that should be performed only in expert centers. Patients with high preoperative PVR are at increased risk of perioperative complications.
Keywords: cardiac; coronary artery bypass grafting; CABG; pulmonary vascular resistance/hypertension; cardiopulmonary bypass; CPB